Predicting Behavior Assessment System for Children–Second Edition Self-Report of Personality Child Form Results Using the Behavioral and Emotional Screening System Student Form: A Replication Study With an Urban, Predominantly Latino/a Sample. (October 2014) - Kiperman, Sarah; Black, Mary S.; McGill, Tia M.; Harrell-Williams, Leigh M.; Kamphaus, Randy W.
This study assesses the ability of a brief screening form, the Behavioral and Emotional Screening System–Student Form (BESS-SF), to predict scores on the much longer form from which it was derived: the Behavior Assessment System for Children–Second Edition Self-Report of Personality–Child Form (BASC-2-SRP-C). The present study replicates a former study included in the BESS manual with an entirely new sample. Participants included 252 students from a large, urban, Southwestern U.S. city school district in the third through fifth grades. The sample's ethnic majority was Hispanic (81.7%). Results revealed high specificity and negative predictive values between the screener and omnibus form, suggesting a child who identifies as not "at-risk" on the BESS-SF will likely identify as not "at-risk" on the BASC-2-SRP-C domains. These results effectively replicate the previous findings with a new sample of largely Hispanic (Latino/a) students from a large urban school district.